Factors impacting university students’ quality of life - Munir Ibn Mahin; Md. Shamsur Rahman; Sk Mustafizur Rahman; Fahmida Binte Ilias; Md. Mehedi Hasan; Mafia Akter; Abdul Rabbi Mredul (PLoS ONE, 2025)
Introduction Quality of life (QoL) is a broad multidimensional concept that incorporates a person’s physical health, psychological well-being, social relations, and environmental factors. Although previous studies have explored QoL among students in health-related disciplines, limited research has assessed QoL in students from diverse academic programs in Bangladesh. This study sought to assess the QoL of University students in Bangladesh and to identify the key factors that determine it. Methods In this cross-sectional study, 417 students were recruited from Daffodil International University. Data were obtained using the WHOQoL-BREF, Pittsburgh Sleep Quality Index (PSQI), Rosenberg Self-Esteem Scale (RSES), and a structured questionnaire that included information pertaining to sociodemographic and lifestyle variables. Results The highest mean score was observed in the social relationships domain (62.93%), while the environmental health domain had the lowest (58.07%). Students who were physically active and had normal self-esteem reported significantly higher scores across physical and psychological health domains. Poor sleep quality, low self-esteem, and lack of exercise were consistently associated with lower QoL scores, particularly in the physical, psychological, and social domains. Female students also reported significantly lower scores than males in three of the four domains. The most consistent and strongest predictors of quality of life across domains were self-esteem and sleep quality, followed by gender, physical activity, and screen time. Conclusion The findings highlight the significant impact of emotional, behavioral, and lifestyle factors on the quality of life of university students. These understandings reinforce the need for campus-based interventions that prioritize mental health support, encourage regular physical exercise, and promote sleep hygiene. Such efforts are essential to enhancing overall student well-being and fostering a healthier, more resilient academic community.